Die veränderte Beschäftigungspraxis in Japan in den letzten zwanzig Jahren - Tonai, Kazuhiro (Zeitschrift für Japanisches Recht, 2005)
In the past, employees of Japanese large-scale enterprises worked for the same company until they reached retirement age (lifelong employment), while wages were raised according to the duration of employment (seniority). In the last 20 years, though, this employment policy has gone through fundamental changes. This article discusses those changes and their background. In the nineties, many companies reduced staff, which forced employees to change jobs or even left them unemployed. Globalization reinforced competition between companies, and deregulation put employers in a position to carry out rationalization measures. The Ministry of Health and Work took several measures to soften those hardships. The ministry founded a Center for the Stabilization of Employment and amended some laws. For instance, it was no longer forbidden to charge commission for placement, and a new law on company pension schemes was enacted in order to avert losses due to redundancy. Discriminatory treatment because of age was prohibited by law. Further legislative changes referred to loan employment; to temporary employment contracts; to the splitting of companies; and to stimulation of staff cuts by means of tax allowances. At present, the number of atypical employment contracts such as parttime or loan employment is rising. Employers are outsourcing their staff by means of loan employment or fictitious self-employment. By that, they reduce the number of core workers. The system of lifelong employment has partly been replaced by the model of premature retirement and by the development that young employees are leaving their first working position after a short period of time. Management of permanent staff is individualized, e.g., contract terms and working times vary. Payment systems are becoming more and more performance-oriented, which displaces the principle of seniority. Many executives can only keep their position until a limit of about 55 years of age. Even though companies of automobile and electronics industries have made profits in the past few years, the average labor cost level is dropping continuously. Those companies don’t share profits with their employees, but rather stop regular wage raises. Financial disadvantages through job change and the fact that there are fewer core workers who benefit from the principle of seniority also lower the average wage level. Employers were able to enforce those innovations unilaterally because labor unions have but few possibilities to take influence and enforce their requests. But employers will face new problems. Loyalty of employees will decrease, which will make company planning less predictable. In the future, politics should maintain protective regulations against dismissal in order to avoid involuntary retirements. Also, the general acceptance of vocational qualifications and standards should be increased. This would soften disadvantages incurred by job change and thus support voluntary job change. Furthermore, the author recommends that politics should abolish the principle of seniority; prohibit age discrimination during the recruitment process; and reduce present differences between core workers and other employees. (The Editors)